Highly loaded hydroxyapatite microsphere/ PLA porous scaffolds obtained by fused deposition modelling. Issue 2 (1st February 2019) - Esposito Corcione, Carola; Gervaso, Francesca; Scalera, Francesca; Padmanabhan, Sanosh Kunjalukkal; Madaghiele, Marta; Montagna, Francesco; Sannino, Alessandro; Licciulli, Antonio; Maffezzoli, Alfonso
Abstract: The goal of the work was the manufacturing of hydroxyapatite microsphere/polylactic acid (PLA) scaffolds by means of fused deposition modelling (FDM). Micrometer-sized hydroxyapatite spheres synthesized by spray drying (sdHA), were dispersed in PLA by extrusion compounding. Composite filaments were obtained from extrusion which were used in FDM 3D printing for the production of macroporous scaffolds. The sdHA microspheres were used in the composite in order to improve the biomimicry and the bioactivity of the 3D printed scaffold to increase the bone regeneration capacity. Morphological, thermal, physical and mechanical characterizations were performed on the 3D printed composites. Pure PLA scaffolds were 3D printed and used as a reference. Thermal analyses, TGA and DSC evidenced that the glass transition temperature and the degree of crystallinity of PLA were not influenced by the presence of sdHA. Morphological analysis showed a smooth surface of the printed samples when pure PLA was used. A rough surface was found on the PLA/sdHA composites, confirming, the homogeneous dispersion of the ceramic phase in the polymeric matrix. The higher porosity of the composite samples compared to PLA ones, most likely caused a decrease of the mechanical performances of the PLA/sdHA scaffolds. Composite scaffolds displayed stiffness values compatible with that of bone tissue.